Propuesta de indicadores en el proceso de inmatriculación de camiones y su relación con la satisfacción del cliente en Divemotor Trujillo, 2016 - Zavaleta Yparraguirre, Diego Alonso (2018)
The objective of this research work is to determine the relationship of the proposed indicators in the process of truck registration with customer satisfaction in Divemotor Trujillo, 2016. After realizing the problematic reality, the research problem has been formulated: How does the proposal of indicators in the truck registration process relate to customer satisfaction in DIVEMOTOR Trujillo, 2016?. To collect the data, the company's information was taken into account, during the period from July to December 2016, Divemotor made a sale of 89 trucks, of which it was calculated and obtained a sample of 72 customers. A survey was formulated and applied to determine customer satisfaction, followed by the formulation of time control indicators and compliance percentage at each stage of the enrollment process. Having the database of both variables, we proceeded to the application of data analysis to find its relationship coefficient and determination between the two concepts, as a result of which 93.97% and 88.3% respectively were obtained. Obtained the results and following the scientific method the analysis and the discussion have been carried out, arriving to demonstrate the validity of the proposed hypothesis: "The proposal of indicators in the process of inmatriculation of trucks, has a high positive relation in the satisfaction of the client in DIVEMOTOR Trujillo, 2016.” Finally, the conclusions and recommendations have been formulated. Given the main objective, it is determined that the number of days elapsed in the enrollment process and customer satisfaction are 93.97% related, where said percentage indicates a positive high association. In the same way, this correlation coefficient indicates that the model is adequate due to being> = 0.70. In addition, the number of days elapsed in the registration process explains customer satisfaction in 88.3%.